Empowering Sustainable Tourism: A Health-Centric and Self-Sustaining Village Program (A Case Study in Sawahan Village, Watulimo Subdistrict, Trenggalek Regency) - Khambali; Rachmaniyah; Fitri Rokhmalia; Hilmi Yumni (Frontiers in Community Service and Empowerment, 2023)
Sawahan Village, Watulimo Subdistrict, Trenggalek Regency, is renowned as a durian forest tourism area. However, residents living near the river basin often complain about the odor due to the frequent presence of garbage along the river. The methods employed include introducing a chlorine diffuser device, supporting the development of the tourism village, promoting self-sufficiency, providing education on waste management through the Takakura method, and establishing a Waste Bank, healthy settlements, and a Clean and Healthy Behavior (CHB) program through Family Action Plans (FAP). The results of the community service in 2022 showed that the physical and chemical parameters of water in Sawahan Village met the required standards. However, the total coliform microbiological parameter at the source did not meet the standards as it exceeded 65 CFU/100 ml, and the Escherichia coli parameter at the source was 3 CFU/100 ml. Therefore, in the 2023 community service project, an Appropriate Technology (AT) called the chlorine diffuser. Assistance was provided for the operation and maintenance of the Clean Water Facility (CWF) by teaching the use of calcium hypochlorite through a chlorine diffuser. Through educational activities, the highest increase in knowledge among the community was related to waste sorting through the Waste Bank, with 10 individuals (20%) initially understanding waste separation, which then increased to 48 individuals (96%). The greatest improvement in community behavior regarding CHB in the FAP was observed in handwashing facilities, with 18 individuals (36%) having access to proper handwashing facilities far from pollutants, which later increased to 50 individuals (100%). INDEX TERMS : Community service, clean water facility, water management, healthy settlements